Fetal exposure to polybrominated diphenyl ethers and the risk of hypospadias: focus on the congeners involved. Issue 4 (August 2019) - Koren, G.; Carnevale, A.; Ling, J.; Ozsarfati, J.; Kapur, B.; Bagli, D.
Summary: Background: Polybrominated diphenyl ethers (PBDEs) are widely used flame retardants, and their endocrine-disrupting properties have focused growing attention regarding their teratogenic potential. We have recently documented that mothers of children born with hypospadias had been exposed to statistically higher levels of PBDE during pregnancy than mothers of healthy controls. However, it is not known which congeners of PBDE are associated with this putative teratogenic effect. Objectives: To identify PBDE congeners associated with increased risk for hypospadias. Study methods: Hair samples from mothers were analyzed and compared between hypospadias cases and healthy controls for eight PBDE congeners using gas chromatography mass spectrometry (GC/MS). Polybrominated diphenyl ether levels were measured in the 0- to 3-cm segment closest to the skull of maternal hair as a proxy for in utero exposure of mothers who lived in the same environment for the duration of their pregnancy. Results: Median maternal hair levels of five PBDE congeners (28, 47, 99, 153, and 154) and of total PBDE (∑PBDE) were significantly higher among mothers of infants with hypospadias ( n = 152) than among controls ( n = 64). Apparent greater differences in the lower brominated congeners, especially in BDE-47 and BDE-99, may be due to the fact that they had been used in larger amounts, and their persistence properties confer longer exposure. Conclusions: The majority of the lower brominated PBDE congeners measured in maternal hair exhibited higher PBDE body burden during pregnancy in mothers of infants who were born with hypospadias.